ANCA‐associated neuropathy in systemic sclerosis: A case report and review of literature. Issue 2 (2nd February 2021) - Takenaka, Kayo; Takeichi, Takuya; Nishi, Ryoji; Suzuki, Masashi; Koike, Haruki; Katsuno, Masahisa; Ogawa‐Momohara, Mariko; Muro, Yoshinao; Akiyama, Masashi
Abstract: Systemic sclerosis (SSc) is a multi‐system autoimmune disease. Anti‐neutrophil cytoplasmic antibodies (ANCA) are autoantibodies directed against enzymes found within primary granules of neutrophils and lysosomes in monocytes. Although up to 12% of SSc patients have ANCA, only a minority of these patients develop an overlap syndrome with ANCA‐associated vasculitis. We summarize previous reports on SSc patients with ANCA‐associated neuropathy. In all the reported cases, the SSc diagnosis preceded the ANCA‐associated neuropathy diagnosis. Seven of the eight patients with limited cutaneous SSc had interstitial lung disease (ILD). Thus, patients with ANCA‐associated neuropathy in lSSc may be prone to complication with ILD. Abstract : We report a Japanese female patient suffering from SSc complicated with ANCA‐associated neuropathy, and we summarize previous reports on SSc patients with ANCA‐associated neuropathy. Seven of the eight patients with limited cutaneous SSc had interstitial lung disease (ILD). Thus, patients with ANCA‐associated neuropathy in lSSc may be prone to complication with ILD.